Cerebral Visual Impairment and the Association with Cerebral Palsy. - Gagnon, Victoria; Lyons, Stacy; Kran, Barry (Optometry & Visual Performance, 2022)
Background: Approximately 60-70% of children with cerebral palsy also display cerebral visual impairment, both of which often share common origins that can involve the retrogeniculate visual pathways. The purpose of this case report is to explore the association of cerebral palsy and cerebral visual impairment, as well as the ocular manifestations typically present in children with cerebral palsy. Case Report: A three-year-old full-term Caucasian male with spastic quadriplegia presented for a clinical functional low vision evaluation in order to determine how to optimize his visual learning environment. Despite normal MRI scans, normal EEG, and a healthy anterior visual pathway, he presented with severely reduced vision, slightly reduced contrast sensitivity, variable strabismus, oculomotor impairment, a bilateral congruous inferior field defect, and visual perceptual dysfunction. Completion of the Teach CVI/Ortibus CVI Survey Level 1 by the patient's parents and nurse revealed 4/6 screening items suspicious of CVI and 10/19 answers suspicious of CVI. The diagnosis of CVI was most consistent with the patient's level of visual function and inability to sustain the use of vision for a task, as well as the response to the CVI survey. The family was given extensive education on how to optimize the patient's visual function and was recommended to undergo a learning media assessment from a teacher of the visually impaired. Conclusions: The clinical diagnosis of cerebral palsy should include not only the characteristics of the motor aspects of the disorder but also the neuro-ophthalmological and perceptual visual aspects that have been shown to be present in a majority of cases. Early intervention and rehabilitation of visual impairments, including CVI, through a multidisciplinary approach can contribute to the improvement of the motor impairments in cerebral palsy and lead to a better overall prognosis.